2014
DOI: 10.1016/j.marpolbul.2014.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced methane emissions from oil and gas exploration areas to the atmosphere – The central Bohai Sea

Abstract: a b s t r a c tThe distributions of dissolved methane in the central Bohai Sea were investigated in November 2011, May 2012, July 2012, and August 2012. Methane concentration in surface seawater, determined using an underway measurement system combined with wavelength-scanned cavity ring-down spectroscopy, showed marked spatiotemporal variations with saturation ratio from 107% to 1193%. The central Bohai Sea was thus a source of atmospheric methane during the survey periods. Several episodic oil and gas spill … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 57 publications
3
11
0
Order By: Relevance
“…However, the locations of DO-deficit areas detected in this study were similar to the DO-deficient zones previously outlined by Zhao et al (2017) and Wei et al (2019). The atmospheric CH 4 mixing ratio in this study (1.89 ± 0.05 ppmv) is much lower than in our previous results from measurements in the central Bohai Sea in July 2012 (2.07 ppmv, Zhang et al, 2014), probably also due to the dilution effect of the three typhoons, which originated from the adjacent open ocean, i.e., the western North Pacific Ocean. However, this field-measured result is slightly higher than the globally averaged marine surface mean value for August 2018 (1.85 ppmv 2 ).…”
Section: Comparisons With Results In the Literaturesupporting
confidence: 86%
See 3 more Smart Citations
“…However, the locations of DO-deficit areas detected in this study were similar to the DO-deficient zones previously outlined by Zhao et al (2017) and Wei et al (2019). The atmospheric CH 4 mixing ratio in this study (1.89 ± 0.05 ppmv) is much lower than in our previous results from measurements in the central Bohai Sea in July 2012 (2.07 ppmv, Zhang et al, 2014), probably also due to the dilution effect of the three typhoons, which originated from the adjacent open ocean, i.e., the western North Pacific Ocean. However, this field-measured result is slightly higher than the globally averaged marine surface mean value for August 2018 (1.85 ppmv 2 ).…”
Section: Comparisons With Results In the Literaturesupporting
confidence: 86%
“…Spatiotemporal variations in [CH 4 ] and thereby sea-to-air CH 4 fluxes have been previously investigated by Li et al (2010), Zhang et al (2014), and Zang (2018), showing that the Bohai Sea is usually supersaturated with CH 4 , with moderate sea-to-air CH 4 fluxes from 0.8 to 53.9 µmol m −2 d −1 . However, so far, there have been no studies relating the sea-to-air CH 4 flux to multiple sources in this area, although several earlier studies showed that river discharges and oil-gas leakages contributed to the Bohai Sea CH 4 release (Gu et al, 2011;Zhang et al, 2014).…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…However, the mechanisms governing the fate of methane and other hydrocarbons into the water column are still under debate, and their probability to reach the atmosphere seems to be site-dependent [57][58][59][60][61][62][63][64]. Accordingly, although difficult, quantifying the contribution of oceanic methane to the global atmospheric budget is crucial, and this necessarily requires knowledge of local methane fluxes from submarine seeps as input.…”
Section: Introductionmentioning
confidence: 99%